Threat‐oriented security framework in risk management using multiagent system. (7th June 2012) - Bedi, Punam; Gandotra, Vandana; Singhal, Archana; Narang, Himanshi; Sharma, Sumit
SUMMARY: Present day sophisticated and innovative attacks have resulted in exponentially increasing security problems. This paper therefore presents a three‐phased threat‐oriented security model to meet the above security challenges as a part of proactive risk management. This model is based on a spiral process for software development because it is a risk driven approach and provides an incremental method for a progressively growing system with decreasing risk. Integration of threat management during the development process in the proposed work provides necessary security cover against both unforeseen and known threats. Identification of these threats has been made possible by fusion of a threat modeling process and research honeytokens in conjunction with a statistical model in the first phase. Necessary security measures to mitigate the above identified threats have been adopted in the second phase using multiagent system planning. Risk reduction as a result of adoption of countermeasures has been evaluated in the third phase using meta‐agents in association with fuzzy logic in a multiagent environment. The proposed proactive measures of this model have been demonstrated with a case study on 'Online Banking' to show its feasibility and has been implemented using Java Agent Development Environment, Apache Tomcat Server, with MySQL Server at the backend. Copyright © 2012 John Wiley & Sons, Ltd.